Green Tea : The Delicious Everyday Health Drink - Oppliger, Peter (Saffron Walden C.W. Daniel Company, 1998)
Trained naturopath Peter Oppliger writes of the therapeutic benefits of drinking green tea, well-documented from the year 800 AD when the custom of drinking green tea was introduced to Japan from China by Buddhist monks
Include Color Illustration, Bibliography and Index
Keywords: Tea--Health aspects -- Tea--Therapeutic use -- Cooking (Tea)